British Catholics' commercial strategies in times of international warfare (1688–1705). Issue 1 (2nd January 2017) - Pizzoni, Giada
ABSTRACT: This article investigates the British Catholic merchants' commercial strategies during the Nine Years War (1689–1697) and the War of the Spanish Succession (1701–1713). By focusing on the tactics deployed by John Aylward and his partners in France and England, I argue that Catholicism fundamentally sustained Aylward's trade by ensuring access to various markets and safer commercial plans. Catholicism had not only an economic dimension and Catholics in trade proved non-communal, working with co-religionists, family but also with non-Catholics in order to pursue profits. This article tells us how Catholicism, despite being a political and social impairment, was the key to success in commerce. It contributes to recent scholarship on religious minorities in trade and on how commerce functioned in the English Channel and in European waters at times of warfare.